Two-Star Fix Without Use of Altitude Difference Method - Kotlarić, Stjepo M. (The International Hydrographic Review, 2015)
This paper deals with a direct method for computation of the coordinates of a ship’s position from the observation of two selected stars without the need to use the altitude difference method known as the Marcq St. Hilaire method. The St. Hilaire method is the one most generally used in the practice of navigation today. This method was worked out ninety-five years ago and during this relatively long period of time no modifications to it have been made except in the way of computing altitude and azimuth. Many the computation of altitude and azimuth : one such was devised by the author in 1958 and under the title “Tables K 1” was published by the Yugoslavian Hydrographic Institute. But the St. Hilaire method is an indirect one, since once the altitudes and azimuths of two celestial bodies have been computed it is necessary to carry out an additional procedure (either graphical or mathematical) in order to obtain the coordinates of the observed position. Thus the availability of a direct method is of interest.